2012
DOI: 10.1007/s00210-012-0795-2
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine prevents cardiac gap junction uncoupling

Abstract: Desipramine seems to prevent the uncoupling of cardiac gap junctions and ischemia-related increase in dispersion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This previous study also demonstrated that hypoxia alone increases pS368-Cx43 expression. On the other hand, other studies have also reported a reduction in pS368-Cx43 induced by acidosis (5,23,34). Additionally, dynamic responses in Cx43 expression and phosphorylation during ischemia have also been previously reported.…”
Section: Gjc In Ischemiamentioning
confidence: 93%
“…This previous study also demonstrated that hypoxia alone increases pS368-Cx43 expression. On the other hand, other studies have also reported a reduction in pS368-Cx43 induced by acidosis (5,23,34). Additionally, dynamic responses in Cx43 expression and phosphorylation during ischemia have also been previously reported.…”
Section: Gjc In Ischemiamentioning
confidence: 93%
“…Structure-activity relations together with molecular modeling, and two-dimensional NMR spectroscopy revealed that AAP10 has a semicyclic structure like a horseshoe, which is due to the two Pro residues (Dhein et al, 2010;Dhein, 1998, 2001). Moreover, it could be shown that [ 14 C]AAP10 binds to a membrane protein of rabbit cardiomyocyte membranes with a K d in the order of 0.3-0.9 nM and maximum binding B max in the order of ;42.5 pmol/mg (Jozwiak et al, 2012). The finding of the semicyclic structure and the identification of the essential chemical moieties Dhein, 1998, 2001) led to the idea of replacing some of the amino acids by D-amino acid versions.…”
Section: B Peptide Modulators Of Connexin Channelsmentioning
confidence: 99%
“…This leads to the question of the biochemical mechanisms of action of antiarrhythmic peptides. First of all, it has been shown that AAP10 and rotigaptide binds to a membrane protein with a K d in the range of 0.1-0.9 nM [[ 14 C]AAP10 Jozwiak et al, 2012); [ 125 I]di-I-AAP10 (Jørgensen et al, 2005)]. A 200-kDa membrane protein could be isolated from cardiac tissue by affinity chromatography and cross-linking techniques (Weng et al, 2002), but its identity was not determined.…”
Section: B Peptide Modulators Of Connexin Channelsmentioning
confidence: 99%
“…Consistently, spermine, an endogenous polyamine with the ability to exert antidepressant effects (Limon, Mamdani, Hjelm, Vawter, & Sequeira, ), increases astroglial intercellular communication by interacting with gap junctional channels and is inhibited by gap junction blockers (Benedikt et al, ). Interestingly, the TCA desipramine prevents acidosis‐induced uncoupling and ischemia‐related loss of membrane Cx43 and Cx43 dephosphorylation in isolated hearts (Jozwiak et al, ). Thus, antidepressant drugs may exert their effects, in part, by increasing Cx43 expression or coupling.…”
Section: Gap Junctionsmentioning
confidence: 99%